Investigation of seasonal variation of compensation parameter and absorption Ångström Exponent of aerosol after loading correction over a remote station in north-east India. (1st September 2019) - Barman, Nilamoni; Roy, Rakesh; Saha, Biswajit; Kundu, S.S.; Borgohain, Arup; De, Barin Kumar; Guha, Anirban
Abstract: One of the extensively used methods for aerosol mass concentration measurement is the optical filter method used in Aethalometer. Due to the aerosol loading and multi scattering effect, there are uncertainties that can lead to underestimation or overestimation of aerosol concentration and measurement of the absorption coefficient. To overcome such uncertainties, a data correction method has been adopted in the present work. During the winter, pre-monsoon and post-monsoon seasons, Aethalometer underestimated black carbon (BC) concentration by 8 ± 1%, 11 ± 1%, and 10.5 ± 0.2%, due to the higher aerosol deposition. While in the monsoon season, underestimation of 5.5 ± 2% is observed because of the presence of bigger scattering nature aerosol. For 70% of days, found a positive correlation between the compensation parameter ( k 880 ) and wavelengths, which indicated the dominance of the smaller aerosol particles. While 30% of days have a negative correlation due to the bigger aerosol particle. In the winter, pre-monsoon and monsoon seasons, the absorption coefficient at 370 nm was 86%, 90%, and 93% higher than that of 880 nm due to the higher biomass burning emissions. The absorption Ångström exponent (α 370-880 ) was 1.02 for fossil fuel burning and the corresponding k 880 was 0.0037. In the winter and post-monsoon seasons, BC emissions from fossil fuel combustion dominated over the BC emitted by biomass burning emissions with α 370-880 < 1.1, whereas α 370-880 is found to be more than 1.2 during the pre-monsoon and monsoon seasons due to the higher biomass burning. Highlights: Transported and local aerosols have an impact on the BC concentration at the site. Transported and local aerosols affect the compensation parameter. Absorption Ångström Exponent increases from 1 to 1.5 at the station.